PFC Simulation Study on Time-dependent Deformation Failure Properties and Energy Conversion Law of Sandstone under Different Axial Stress - Wang, Yu; Liu, Qi (Periodica Polytechnica Civil Engineering, 2022)
Rock burst mostly happens in deep rock engineering, which obviously performs obvious time-dependent destruction and releases huge energy. Thus, the uniaxial compressive time-dependent deformation failure tests of sandstone under different axial stress are conducted and the optimized Parallel-bonded stress corrosion (PSC) model is established based on PFC method. The results show that tension micro-cracks are the direct reason of rock bearing capacity reduction during the whole failure process. The time-dependent deformation stage is composed of the initial strain stage, the steady-state strain stage and the accelerated strain stage. As the axial stress increases, rock mass enters into the accelerated strain stage more quickly and the strain amount of time-dependent deformation stage decreases. From the comparison of energy conversion between PFC simulation and experiments, the higher elastic strain energy will be accumulated and the less dissipation energy will be produced while the axial stress increases when reaching the failure point. After the failure point, the elastic strain energy has a small increase because the strain rate changes faster than the failure relaxation rate. Based on the calculation results of residual elastic energy index (AEF), the rock burst shows a tendency that from weakness to moderation as the axial stress increases. The research results will provide a certain reference in predicting the rock burst.